The role of gut microbiota and its metabolites short-chain fatty acids in food allergy - Chen Chen; Chenglong Liu; Ke Zhang; Wentong Xue (Food Science and Human Wellness)
Emerging evidence indicated that the increase in food allergy (FA) over the past few decades was associated with the abnormal compositional and metabolic changes of gut microbiota. Gut microbiota played a vital role in maintaining the homeostasis of the immune system and the dysbiosis of gut microbiota promoted the occurrence of FA. Recent research suggested that short-chain fatty acids (SCFAs), the main metabolites derived from gut microbiota, contributed to FA protection. Herein, we provided a comprehensive review on the relationship between gut microbiota and FA. The multifaceted mechanisms underlying beneficial effects of gut microbiota composition/metabolites on the regulation of diverse cellular pathways in intestinal epithelial cells, dendritic cells, innate lymphoid cells, T cells, B cells and mast cells in the immune system were discussed systematically. These findings emphasized the positive function of gut microbiota in FA and provided novel ideas for the treatment or prevention of FA in the future.